THE BIRDS AND THE BEES ONLINE: UNDERSTANDING AMERICAN ONLINE SEX-ED SITES - Ross, Janet Nalubega; Walker, Shawn (AoIR Selected Papers of Internet Research, 2019)
The goal of this study is, looking over time and across different platforms what is the nature of the content of adolescent sexual health education provided through online websites and social networking sites (SNS). Sexuality is a critical component of adolescent development, and to aid in sexual development, the United Nations Educational, Scientific and Cultural Organization (UNESCO), and the World Health Organization (WHO) recommends that adolescents globally have access to comprehensive sexual health education because it contributes positively their future sexual and reproductive health (UNESCO, 2018). In the United States, starting in 1981 with Adolescent Family Life Act (AFLA) sexual health education has relied heavily on Abstinence-Only curricula, with the goal of teaching adolescents to reduce risky sexual behaviors, such as having unprotected sex, having multiple sexual partners and young age of sexual debut by remaining sexually abstinent until marriage (Dixon-Mueller, 1993; Saul, 1998). Looking over time and across online platforms, the goal of this study is to determine; 1). How is sexual health education online structured and what topics are covered? 2). How has online sexual health education over time responded to government mandates on sexual health and sexuality in general? 3). How does the presentation of sexual health information change across the different platforms? and 4). How do online sexual health education handle topics such pleasure and desire for underrepresented groups?